Cloudy days ahead: Cross-border evidence collection and its impact on the rights of EU citizens. Issue 3 (September 2019) - Siry, Lawrence
In recent years, the development of cloud storage and the ease of cross-border communication have rendered the area of evidence collection particularly difficult for law enforcement agencies (LEAs), courts and academics. Evidence related to a criminal act in one jurisdiction might be stored in a different jurisdiction. Often it is not even clear in which jurisdiction the relevant data are, and at times the data may be spread over multiple jurisdictions. The traditional rules related to cross-border evidence collection, the mutual legal assistance treaty (MLAT) regimes, have proved to be out-dated, cumbersome and inefficient, as they were suited for a time when the seeking of cross-border evidence was more infrequent. In order to tackle this problem, the United States has enacted the Clarifying Lawful Overseas Use of Data Act, which gives extraterritorial e-evidence collection powers to US courts. Simultaneously, the European Union (EU) has proposed similar sweeping changes which would allow for LEAs in Member States to preserve and collect cloud-based evidence outside of the MLAT system. This article critically evaluates these developments from the perspective of the impact on the rights of EU citizens.